Ni / Fe3O4 composite material, electrode and preparation method thereof, alkaline electrolytic bath and method for producing hydrogen by electrolyzing water

By using Ni/Fe3O4 composite material as a catalytic material, the magnetothermal effect and conductivity are used to reduce the activation energy of the water electrolytic reaction, and the problems of low hydrogen production efficiency and high energy consumption in traditional alkaline electrolytic cells are solved, thereby achieving efficient hydrogen production.

CN120158775AActive Publication Date: 2025-06-17JIANGSU TRINA GREEN HYDROGEN TECHNOLOGY CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510639500.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-19
Publication Date
2025-06-17
Estimated Expiration
2045-05-19

AI Technical Summary

Technical Problem

The hydrogen production efficiency of traditional alkaline electrolytic cells is low and the energy consumption is high, mainly due to the low operating current density and the high overpotential of water electrolytic reaction.

Method used

Ni/Fe3O4 composite material is used as the catalytic material. By coupling nickel element and iron tetroxide, the magnetothermal effect of iron tetroxide and the H*/OH* conversion site provided by nickel element are used to reduce the activation energy of the water electrolytic reaction, thereby reducing the overpotential and improving the hydrogen production efficiency.

Benefits of technology

It significantly reduces the activation energy of the electrolytic reaction, reduces the hydrogen evolution overpotential, improves the hydrogen production efficiency, reduces energy consumption, and does not need to increase the operating temperature of the electrolytic cell, avoiding diaphragm damage and corrosion of the electrolytic cell body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120158775A_ABST
    Figure CN120158775A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalytic materials, in particular to a Ni / Fe3O4 composite material, an electrode, a preparation method of the electrode, an alkaline electrolytic bath and a method for producing hydrogen by electrolyzing water. The Ni / Fe3O4 composite material comprises secondary particles, the secondary particles comprise stacked primary particles, each primary particle comprises an inner core and a shell arranged on the surface of the inner core, the inner core comprises ferroferric oxide, and the shell comprises nickel elementary substance. According to the Ni / Fe3O4 composite material, ferroferric oxide is used as an inner core, and the surface of the inner core is coated with a nickel elementary substance shell, so that the conductivity of the Ni / Fe3O4 composite material is relatively good; when the catalyst is used as a catalytic material for preparing an electrode in an alkaline electrolytic cell, and is used for producing hydrogen by electrolyzing water, the activation energy of a water electrolysis reaction can be reduced, so that the overpotential of the water electrolysis reaction is reduced, the hydrogen production efficiency is further improved, the operating temperature of the electrolytic cell does not need to be increased, the energy consumption can be reduced, a diaphragm is basically not damaged, and a cell body is not corroded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of catalytic materials, and in particular to a Ni / Fe3O4 composite material, an electrode and a preparation method thereof, an alkaline electrolytic cell and a method for producing hydrogen by electrolyzing water. Background Art

[0002] Alkaline electrolyzers, including electrolyzer bodies, electrodes, diaphragms, electrolytes and other components, play a vital role in large-scale hydrogen production. However, traditional alkaline electrolyzers have low hydrogen production efficiency and high energy consumption.

[0003] Therefore, it is necessary to improve the traditional technology. Summary of the invention

[0004] Based on this, the present application provides a Ni / Fe3O4 composite material, an electrode and a preparation method thereof, an alkaline electrolyzer and a method for producing hydrogen by electrolyzing water, which can effectively improve the efficiency of hydrogen production.

[0005] The technical solution of this application to solve the above technical problems is as follows.

[0006] In a first aspect, the present application provides a Ni / Fe3O4 composite material, comprising secondary particles, wherein the secondary particles comprise stacked primary particles, wherein the primary particles comprise an inner core and an outer shell disposed on the surface of the inner core, wherein the inner core comprises ferrosoferric oxide, and the outer shell comprises nickel.

[0007] In some of the embodiments, in the Ni / Fe3O4 composite material, the particle size of the secondary particles is 10 μm-100 μm.

[0008] In some of the embodiments, in the Ni / Fe3O4 composite material, the particle size of the primary particles is 45 nm~125 nm.

[0009] In some embodiments, in the Ni / Fe3O4 composite material, in the primary particles, the mass ratio of the ferroferric oxide to the nickel element is 1:0.2-3;

[0010] And / or, the particle size of the ferrosoferric oxide is 30 nm to 80 nm.

[0011] In some embodiments, in the Ni / Fe3O4 composite material, the Ni / Fe3O4 composite material is subjected to a current density of 500 mA / cm 2 The hydrogen evolution overpotential is ≤335 mV, and the oxygen evolution overpotential is ≤433 mV.

[0012] The second aspect of the present application provides a method for preparing a Ni / Fe3O4 composite material, comprising the following steps:

[0013] Mix Ni / Fe3O4 powder, binder and solvent to obtain a slurry; the Ni / Fe3O4 powder includes a core and a shell provided on the surface of the core, the core includes iron oxide, and the shell includes nickel.

[0014] Perform spray drying and sintering treatment on the slurry in sequence to obtain a Ni / Fe3O4 composite material.

[0015] In some embodiments, in the preparation method of the Ni / Fe3O4 composite material, the temperature of the sintering treatment is 500 °C to 900 °C;

[0016] and / or, perform the sintering treatment under vacuum conditions;

[0017] and / or, the inlet air temperature of the spray drying is 250 °C to 350 °C, the outlet air temperature of the spray drying is 150 °C to 200 °C, and the air flow pressure of the spray drying is 30 kPa to 100 kPa;

[0018] and / or, the Ni / Fe3O4 powder is primary particles;

[0019] and / or, the particle size of the Ni / Fe3O4 powder is 45 nm to 120 nm;

[0020] and / or, the binder includes polyvinyl alcohol;

[0021] and / or, the mass ratio of the binder to the Ni / Fe3O4 powder is 0.002 to 0.006:1;

[0022] and / or, the solvent includes water.

[0023] In some embodiments, in the preparation method of the Ni / Fe3O4 composite material, the preparation of the Ni / Fe3O4 powder includes the following steps:

[0024] Mix iron oxide powder, nickel precursor, reducing agent and pH regulator to carry out hydrothermal reaction, and the nickel precursor is reduced to generate nickel on the surface of the iron oxide powder to prepare Ni / Fe3O4 powder.

[0025] In some embodiments, in the preparation method of the Ni / Fe3O4 composite material, the temperature of the hydrothermal reaction is 80 °C to 120 °C;

[0026] and / or, the nickel precursor includes at least one of nickel chloride, nickel sulfate and nickel nitrate;

[0027] and / or, the mass ratio of the nickel precursor to the iron oxide powder is 0.6 to 8:1;

[0028] and / or, the reducing agent comprises at least one of ethylene glycol, sodium borohydride and sodium citrate;

[0029] And / or, the mass ratio of the reducing agent to the ferroferric oxide powder is 20-30:1;

[0030] And / or, the pH adjuster includes aqueous ammonia;

[0031] And / or, the mass ratio of the pH regulator to the nickel precursor is 2-8:1.

[0032] The third aspect of the present application provides a catalytic material, comprising the Ni / Fe3O4 composite material provided in the first aspect or the Ni / Fe3O4 composite material prepared by the preparation method provided in the second aspect.

[0033] A fourth aspect of the present application provides an electrode, comprising a substrate and a catalyst disposed on the surface of the substrate, wherein the catalyst comprises the catalytic material provided in the third aspect.

[0034] A fifth aspect of the present application provides a method for preparing an electrode, comprising the following steps:

[0035] The Ni / Fe3O4 composite material provided in the first aspect or the Ni / Fe3O4 composite material prepared by the preparation method provided in the second aspect is arranged on the surface of the substrate to prepare an electrode.

[0036] The sixth aspect of the present application provides an alkaline electrolytic cell, comprising an electrolytic cell body, a first electrode, a second electrode and an electrolyte, wherein the electrolyte is disposed in the electrolytic cell body, the first electrode and the second electrode are disposed in the electrolyte, and at least one of the first electrode and the second electrode is the electrode provided in the fourth aspect or the electrode prepared by the preparation method provided in the fifth aspect.

[0037] A seventh aspect of the present application provides a method for producing hydrogen by electrolysis of water, comprising the following steps:

[0038] The alkaline electrolytic cell provided in the sixth aspect is powered to electrolyze water to produce hydrogen.

[0039] In some of the embodiments, the method for producing hydrogen by electrolysis of water further includes applying a magnetic field to the alkaline electrolytic cell during the process of producing hydrogen by electrolysis of water.

[0040] The Ni / Fe3O4 composite material of the present application includes secondary particles, the secondary particles include at least two stacked primary particles, each primary particle includes an inner core and an outer shell arranged on the surface of the inner core, the inner core includes ferroferric oxide, and the outer shell includes nickel. The inner core is made of ferroferric oxide, and the surface of the inner core is coated with a nickel outer shell, so that the conductive performance of the Ni / Fe3O4 composite material is better.

[0041] The Ni / Fe3O4 composite material provided in the present application is used as a catalytic material to prepare electrodes in an alkaline electrolytic cell, and is used to electrolyze water to produce hydrogen. By coupling nickel element and ferroferric oxide, utilizing the magnetocaloric effect of ferroferric oxide, and applying an alternating magnetic field, local heating can be generated. Combined with the H* / OH* conversion sites provided by the nickel element, the activation energy of the water electrolysis reaction can be reduced, thereby reducing the overpotential of the water electrolysis reaction, thereby improving the hydrogen production efficiency. There is no need to increase the operating temperature of the electrolytic cell, which can reduce energy consumption, and basically will not damage the diaphragm or corrode the cell body. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0043] Figure 1 A transmission electron microscope image of Ni / Fe3O4 primary particles provided in one embodiment;

[0044] Figure 2 A mapping diagram of Ni / Fe3O4 primary particles provided in one embodiment;

[0045] Figure 3 A scanning electron microscope image of Ni / Fe3O4 secondary particles provided in one embodiment. DETAILED DESCRIPTION

[0046] The present application will be further described in detail below in conjunction with the embodiments and examples. It should be understood that these embodiments and examples are only used to illustrate the present application and are not used to limit the scope of the present application. The purpose of providing these embodiments and examples is to make the understanding of the disclosure of the present application more thorough and comprehensive. It should also be understood that the present application can be implemented in many different forms, and is not limited to the embodiments and examples described herein. Those skilled in the art can make various changes or modifications without violating the connotation of the present application, and the equivalent form obtained also falls within the protection scope of the present application. For example, the features described or described as part of an embodiment can be combined in another embodiment in a suitable manner to produce a new embodiment. In addition, in the description below, a large number of specific details are given in order to provide a more comprehensive understanding of the present application, and it should be understood that the present application can be implemented without one or more of these details.

[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. The terms used in the description of this application herein are for the purpose of describing embodiments and examples only and are not intended to limit this application.

[0048] Unless otherwise stated or in case of contradiction, the terms or phrases used herein have the following meanings:

[0049] In this application, when it comes to "multiple", "diverse", "multiple times", etc., unless otherwise specified, it means greater than 2 or equal to 2 in quantity. For example, "one or more" means one or greater than or equal to two.

[0050] As used herein, "its combination", "any combination thereof", "any combination mode thereof", etc. include all suitable combination modes of any two or more of the listed items.

[0051] In this application, the "suitable" in "suitable combination mode", "suitable mode", "any suitable mode", etc. is subject to being able to implement the technical solution of this application, solve the technical problems of this application, and achieve the expected technical effects of this application.

[0052] In this application, "preferred", "better", "more preferable", "it is advisable" are only used to describe embodiments or examples with better effects. It should be understood that they do not constitute a limitation on the protection scope of this application. If there are multiple "preferred" in a technical solution, unless otherwise specified and without contradiction or mutual restriction, each "preferred" is independent.

[0053] In this application, "further", "even further", "especially", etc. are used for descriptive purposes and represent differences in content, but should not be understood as a limitation on the protection scope of this application.

[0054] In this application, "optionally", "optional", "optional" mean that it can be either present or absent, that is, it refers to any one of the two parallel options of "present" or "absent". If there are multiple "optional" in a technical solution, unless otherwise specified and without contradiction or mutual restriction, each "optional" is independent.

[0055] In this application, in "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description and should be understood not to constitute a closed limitation on quantity.

[0056] In this application, among the technical features described in an open-ended manner, it includes a closed technical solution composed of the listed features, and also includes an open technical solution containing the listed features.

[0057] In this application, regarding a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the selectable numerical values within this numerical interval is considered continuous, and it includes the two numerical endpoints of this numerical interval (i.e., the minimum value and the maximum value), as well as each numerical value between these two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within this numerical interval, it includes the two endpoint integers of this numerical range, as well as each integer between the two endpoints, which is equivalent to directly listing each integer. When providing multiple numerical ranges to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all sub-ranges subsumed therein. The "numerical value" in this numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. The "numerical interval" is allowed to broadly include numerical interval types such as a percentage interval, a ratio interval, a ratio value interval, etc.

[0058] The temperature parameter in this application, unless otherwise specified, allows for both constant temperature treatment and variation within a certain temperature interval. It should be understood that the so-called constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within a range such as ±5°C, ±4°C, ±3°C, ±2°C, ±1°C are allowed.

[0059] In this application, the term "room temperature" or "normal temperature" generally refers to 4°C to 35°C, such as 20°C ± 5°C. In some embodiments of this application, "room temperature" or "normal temperature" refers to 10°C to 30°C. In some embodiments of this application, "room temperature" or "normal temperature" refers to 20°C to 30°C.

[0060] In this application, regarding the unit of a data range, if the unit is only attached after the right endpoint, it means that the units of the left endpoint and the right endpoint are the same. For example, 3~5 h means that the units of the left endpoint "3" and the right endpoint "5" are both h (hours).

[0061] All documents mentioned in this application are incorporated herein by reference as if each document was individually incorporated by reference. Unless it conflicts with the inventive purpose and / or technical solution of this application, the cited documents involved in this application are incorporated by reference in their entirety and for all purposes. When referring to cited documents in this application, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also incorporated by reference. When referring to cited documents in this application, the examples and preferred methods of the relevant technical features cited can also be incorporated as references into this application, but only to the extent that this application can be implemented. It should be understood that when the cited content conflicts with the description in this application, this application shall prevail or be amended adaptively according to the description of this application.

[0062] The quality or weight of the relevant components mentioned in the specification of the embodiments of this application not only can refer to the specific content of each component, but also can represent the proportional relationship of the quality or weight between each component. Therefore, as long as the content of the relevant components in the specification of the embodiments of this application is scaled up or down proportionally, it is within the scope disclosed in the specification of the embodiments of this application. Specifically, the quality or weight described in the specification of the embodiments of this application can be units well-known in the chemical industry such as μg, mg, g, kg, etc.

[0063] The technical personnel of this application, through a large amount of research and analysis, believe that the reasons for the low hydrogen production efficiency and high energy consumption of traditional alkaline electrolyzers include: the operating current density of traditional alkaline electrolyzers is relatively low, mainly due to the high overpotentials in the hydrogen evolution and oxygen evolution reactions. The overpotential of the water electrolysis reaction is affected by various factors, among which temperature is one of the key factors. Temperature can affect the solution conductivity and the activity of the catalyst, thereby affecting the energy efficiency of the alkaline electrolyzer. As the temperature increases, the solution resistance decreases, the reaction activation energy decreases, the catalytic activity increases, and the catalytic reaction overpotential decreases. However, although increasing the temperature can reduce the water electrolysis reaction voltage and improve the reaction rate of the alkaline electrolyzer, too high a temperature will cause the diaphragm to fail and accelerate the corrosion of the electrolyzer cell body.

[0064] One embodiment of this application provides a Ni / Fe3O4 composite material, which includes secondary particles. The secondary particles include stacked primary particles. The primary particles include a core and a shell provided on the surface of the core. The core includes iron oxide, and the shell includes nickel.

[0065] The Ni / Fe3O4 composite material of this application includes secondary particles. The secondary particles include at least two stacked primary particles. Each primary particle includes a core and a shell provided on the surface of the core. The core includes iron oxide, and the shell includes nickel. With iron oxide as the core and a nickel shell coated on the surface of the core, the Ni / Fe3O4 composite material has good electrical conductivity.

[0066] The Ni / Fe3O4 composite material provided in the present application is used as a catalytic material to prepare electrodes in an alkaline electrolytic cell, and is used to electrolyze water to produce hydrogen. By coupling nickel element and ferroferric oxide, utilizing the magnetocaloric effect of ferroferric oxide, and applying an alternating magnetic field, local heating can be generated without affecting the temperature of the entire electrolytic cell. The H* / OH* conversion sites provided by the nickel element can reduce the activation energy of the water electrolysis reaction, thereby reducing the overpotential of the water electrolysis reaction, thereby improving the hydrogen production efficiency. There is no need to increase the operating temperature of the electrolytic cell, which can reduce energy consumption, and basically does not damage the diaphragm or corrode the cell body.

[0067] In the process of producing hydrogen by electrolysis of water, the higher the operating current density of the alkaline electrolyzer, the faster the hydrogen production rate. However, applying a higher current density may increase the overpotential in the hydrogen and oxygen evolution reactions, resulting in increased operating energy consumption, thereby leading to lower energy efficiency. Using the Ni / Fe3O4 composite material provided in the present application as a catalytic material to prepare electrodes can significantly reduce the activation energy of the electrolysis reaction and reduce the hydrogen evolution overpotential, thereby reducing the operating energy consumption of the alkaline electrolyzer and improving energy efficiency.

[0068] In the core-shell structured Ni / Fe3O4 composite material, the inner core Fe3O4 has excellent magnetocaloric properties, and the shell nickel has excellent electrical conductivity and catalytic activity for water electrolysis reaction. By applying an alternating magnetic field, a local heating effect is generated to reduce the activation energy of the electrolysis reaction.

[0069] It can be understood that the secondary particles include a plurality of stacked primary particles, each of which includes an inner core and an outer shell disposed on the surface of the inner core, the inner core includes ferrosoferric oxide, and the outer shell includes nickel.

[0070] In some of these examples, the particle size of secondary particles in Ni / Fe3O4 composites is 10 μm~100 μm.

[0071] It can be understood that the particle size of the secondary particles includes but is not limited to 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm; in some examples, any two of these point values ​​can be used as end values. The same applies below. Further, the particle size of the secondary particles includes but is not limited to 10 μm~25 μm, 30 μm~50 μm, 60 μm~80 μm, 80 μm~100 μm.

[0072] In some of these examples, the particle size of secondary particles in Ni / Fe3O4 composites is 30 μm~50 μm.

[0073] By controlling the particle size of the secondary particles within an appropriate range, it is possible to avoid having too many undissolved particles in the coating due to a large particle size, which would affect the electrode performance, and to avoid the coating becoming dense due to a small particle size, which would reduce the active area of the electrode and thus affect the electrode performance.

[0074] In some examples, in the Ni / Fe3O4 composite material, the particle size of the primary particles is 45 nm to 125 nm. It can be understood that the particle size of the primary particles includes, but is not limited to, 45 nm, 55 nm, 65 nm, 75 nm, 140 nm, 85 nm, 95 nm, 105 nm, 115 nm, and 125 nm.

[0075] Optionally, the particle size of the primary particles is 45 nm to 100 nm.

[0076] It can be understood that the particle sizes of the secondary particles and the primary particles refer to the absolute particle size, and the absolute particle size refers to the true size of the particles themselves.

[0077] In some examples, in the Ni / Fe3O4 composite material, in the primary particles, the mass ratio of iron oxide to nickel is 1:0.2 to 3.

[0078] It can be understood that the mass ratio of iron oxide to nickel includes, but is not limited to, 1:0.2, 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.2, 1:2.5, 1:2.8, and 1:3.

[0079] Optionally, in the primary particles, the mass ratio of iron oxide to nickel is 1:0.2 to 2. Further, the mass ratio of iron oxide to nickel is 1:1 to 2.

[0080] It can be understood that the mass ratio of iron oxide to nickel in the secondary particles is the same as that in the primary particles.

[0081] In some examples, in the Ni / Fe3O4 composite material, the particle size of iron oxide is 30 nm to 80 nm.

[0082] It can be understood that the particle size of iron oxide includes, but is not limited to, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, and 80 nm.

[0083] In some examples, for the Ni / Fe3O4 composite material, at a current density of 500 mA / cm 2 the hydrogen evolution overpotential ≤ 335 mV and the oxygen evolution overpotential ≤ 433 mV.

[0084] Furthermore, the Ni / Fe3O4 composite material has a current density of 500 mA / cm 2 The overpotential for hydrogen evolution is ≤301 mV, and the overpotential for oxygen evolution is ≤392 mV.

[0085] Furthermore, the Ni / Fe3O4 composite material has a current density of 500 mA / cm 2 The overpotential for hydrogen evolution is 176 mV~301 mV, and the overpotential for oxygen evolution is 233 mV~392 mV.

[0086] It can be understood that the Ni / Fe3O4 composite material provided in this application has a current density of 500 mA / cm 2 The hydrogen evolution overpotential and oxygen evolution overpotential are low, and it can be used to prepare electrodes and to electrolyze water to produce hydrogen, which can effectively improve the hydrogen production efficiency.

[0087] An embodiment of the present application provides a method for preparing a Ni / Fe3O4 composite material, comprising the following steps:

[0088] The Ni / Fe3O4 powder, a binder and a solvent are mixed to prepare a slurry; the Ni / Fe3O4 powder comprises a core and a shell arranged on the surface of the core, the core comprises ferroferric oxide, and the shell comprises nickel;

[0089] The slurry is spray-dried and sintered in sequence to obtain a Ni / Fe3O4 composite material.

[0090] It can be understood that the preparation method of the Ni / Fe3O4 composite material provided in the present application can produce the above-mentioned Ni / Fe3O4 composite material, wherein the Ni / Fe3O4 powder is equivalent to the primary particles in the Ni / Fe3O4 composite material, and the secondary particles are obtained by sintering; that is, in some of the examples, in the preparation method of the Ni / Fe3O4 composite material, the Ni / Fe3O4 powder is the primary particle; further, the particle size of the Ni / Fe3O4 powder is 45 nm~120 nm.

[0091] It can be further understood that the preparation method of the Ni / Fe3O4 composite material provided in the present application and the characteristics of the above-mentioned Ni / Fe3O4 composite material can be mutually applicable.

[0092] In some of the examples, in the method for preparing the Ni / Fe3O4 composite material, the sintering temperature is 500°C~900°C.

[0093] It is understood that the temperature of the sintering treatment includes but is not limited to 500° C., 550° C., 600° C., 650° C., 700° C., 750° C., 800° C., 850° C., and 900° C. It is understood that the powder obtained by the sintering treatment is screened to select the powder with a particle size of 10 μm to 100 μm, which is the secondary particle.

[0094] Further, the sintering treatment time is 4 h to 10 h.

[0095] It can be understood that the sintering treatment time includes but is not limited to 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, and 10 h.

[0096] In some of these examples, in the method for preparing the Ni / Fe3O4 composite material, the sintering treatment is carried out under vacuum conditions.

[0097] Spray drying: The slurry is transported to an atomizer to be atomized into droplets, and the droplets are dried into spherical particles at high temperature.

[0098] In some of these examples, in the method for preparing the Ni / Fe3O4 composite material, the inlet air temperature of spray drying is 250°C to 350°C, the outlet air temperature of spray drying is 150°C to 200°C, and the air flow pressure of spray drying is 30 kPa to 100 kPa.

[0099] In some of these examples, in the method for preparing the Ni / Fe3O4 composite material, the binder includes polyvinyl alcohol.

[0100] It can be understood that the binder is decomposed during the sintering treatment process.

[0101] In some of these examples, in the method for preparing the Ni / Fe3O4 composite material, the mass ratio of the binder to the Ni / Fe3O4 powder is 0.002 to 0.006:1.

[0102] It can be understood that the mass ratio of the binder to the Ni / Fe3O4 powder includes but is not limited to 0.002:1, 0.003:1, 0.004:1, 0.005:1, and 0.006:1.

[0103] In some of these examples, in the method for preparing the Ni / Fe3O4 composite material, the solvent includes water. Further, the mass ratio of the solvent to the Ni / Fe3O4 powder is 50 to 200:1.

[0104] In some of these examples, in the method for preparing the Ni / Fe3O4 composite material, after mixing the Ni / Fe3O4 powder, the binder, and the solvent, it further includes a step of ball milling the obtained mixture.

[0105] In some of these examples, in the method for preparing the Ni / Fe3O4 composite material, the ball milling step further includes a step of adding an antifoaming agent. Optionally, the antifoaming agent includes n-butanol. Optionally, the mass ratio of the antifoaming agent to the Ni / Fe3O4 powder is 0.003 to 0.007:1.

[0106] In some of these examples, the preparation method of the Ni / Fe3O4 composite material includes the following steps:

[0107] After mixing Ni / Fe3O4 powder and water, a binder and an antifoaming agent are added and ball-milled to prepare a slurry.

[0108] The slurry is successively spray-dried, sintered, and sieved to obtain the Ni / Fe3O4 composite material.

[0109] In some of these examples, in the preparation method of the Ni / Fe3O4 composite material, the preparation of the Ni / Fe3O4 powder includes the following steps:

[0110] Mix ferric oxide powder (Fe3O4 nanoparticles), nickel precursor, reducing agent, and pH regulator for hydrothermal reaction. The nickel precursor is reduced on the surface of the ferric oxide powder to generate nickel metal, and Ni / Fe3O4 powder is prepared.

[0111] It can be understood that the present application can prepare Ni / Fe3O4 powder with a core-shell structure by co-precipitation and hydrothermal methods.

[0112] In some of these examples, in the preparation steps of the Ni / Fe3O4 powder, the temperature of the hydrothermal reaction is 80°C to 120°C.

[0113] It can be understood that the temperature of the hydrothermal reaction includes but is not limited to 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C.

[0114] In some of these examples, in the preparation steps of the Ni / Fe3O4 powder, the nickel precursor includes at least one of nickel chloride, nickel sulfate, and nickel nitrate.

[0115] In some of these examples, in the preparation steps of the Ni / Fe3O4 powder, the mass ratio of the nickel precursor to the ferric oxide powder is 0.6 to 8:1.

[0116] It can be understood that the mass ratio of the nickel precursor to the ferric oxide powder includes but is not limited to 0.6:1, 0.8:1, 1:1, 2:1, 2.6:1, 3:1, 4:1, 5:1, 5.3:1, 6:1, 7:1, 8:1.

[0117] In some of these examples, in the preparation steps of the Ni / Fe3O4 powder, the reducing agent includes ethylene glycol.

[0118] In some of these examples, in the preparation steps of the Ni / Fe3O4 powder, the mass ratio of the reducing agent to the ferric oxide powder is 20 to 30:1.

[0119] It is understood that the mass ratio of the reducing agent to the Fe₃O₄ powder includes but is not limited to 20:1, 22:1, 23:1, 24:1, 26:1, 28:1, 30:1.

[0120] In some of these examples, in the preparation step of the Ni / Fe₃O₄ powder, the pH regulator includes ammonia water.

[0121] Using ammonia water as the pH regulator, the pH value of the reaction system can be controlled within a range favorable for the reduction of nickel ions to nickel metal, promoting the reduction of nickel ions to nickel metal.

[0122] In some of these examples, in the preparation step of the Ni / Fe₃O₄ powder, the mass ratio of the pH regulator to the nickel precursor is 2 - 8:1.

[0123] It is understood that the mass ratio of the pH regulator to the nickel precursor includes but is not limited to 2:1, 3:1, 4:1, 6:1, 8:1.

[0124] In some of these examples, in the preparation step of the Ni / Fe₃O₄ powder, in the step of mixing the Fe₃O₄ powder, the nickel precursor, the reducing agent, and the pH regulator, the following steps are included:

[0125] After mixing the Fe₃O₄ powder and the reducing agent, add the nickel precursor and stir, and then add the pH regulator.

[0126] In some of these examples, in the preparation step of the Ni / Fe₃O₄ powder, the Fe₃O₄ powder can be obtained commercially or prepared by oneself; further, the Fe₃O₄ powder includes but is not limited to at least one of chemical coprecipitation method, pyrolysis method, steam oxidation method, etc.

[0127] In some of these examples, the preparation method of the Fe₃O₄ powder includes the following steps:

[0128] Mix a divalent iron precursor, a trivalent iron precursor, a solvent, and a precipitating agent and carry out a hydrothermal reaction to prepare the Fe₃O₄ powder.

[0129] In some of these examples, in the preparation method of the Fe₃O₄ powder, the divalent iron precursor includes at least one of ferrous chloride, ferrous nitrate, and ferrous sulfate.

[0130] In some of these examples, in the preparation method of the Fe₃O₄ powder, the trivalent iron precursor includes at least one of ferric chloride, ferric nitrate, and ferric sulfate.

[0131] In some of these examples, in the preparation method of the Fe₃O₄ powder, the molar ratio of the divalent iron precursor to the trivalent iron precursor is 1:1.5 - 2.

[0132] In some of these examples, in the method for preparing iron oxide powder, the precipitant includes at least one of ammonia water, sodium hydroxide, and potassium hydroxide.

[0133] In some of these examples, in the method for preparing iron oxide powder, the molar ratio of the total mass of the divalent iron precursor and the trivalent iron precursor to the precipitant is 1:0.1 to 0.3.

[0134] In some of these examples, in the method for preparing iron oxide powder, the precipitant is ammonia water. Optionally, the concentration of ammonia water is 1 mol / L to 2 mol / L.

[0135] In some of these examples, in the method for preparing iron oxide powder, the temperature of the hydrothermal reaction is 160°C to 200°C, and the time is 3 h to 6 h.

[0136] In some of these examples, the method for preparing iron oxide powder includes the following steps:

[0137] Mix the divalent iron precursor, the trivalent iron precursor, and the solvent to prepare a mixed solution;

[0138] After heating the mixed solution to 50°C to 60°C, add the precipitant, stir and react until the mixed solution turns black, then stop stirring, and age for 0.5 h to 1 h;

[0139] Perform a hydrothermal reaction on the aged solution.

[0140] It can be understood that after the hydrothermal reaction, it further includes the steps of washing, filtering, and drying the reaction solution in sequence.

[0141] One embodiment of the present application provides the use of the above-mentioned Ni / Fe3O4 composite material or the Ni / Fe3O4 composite material prepared by the above-mentioned method for preparing the Ni / Fe3O4 composite material in the preparation of a catalytic material.

[0142] Another embodiment of the present application provides a catalytic material, including the above-mentioned Ni / Fe3O4 composite material or the Ni / Fe3O4 composite material prepared by the above-mentioned method for preparing the Ni / Fe3O4 composite material.

[0143] It can be understood that the catalytic material provided by the present application, including the above-mentioned Ni / Fe3O4 composite material or the Ni / Fe3O4 composite material prepared by the above-mentioned method for preparing the Ni / Fe3O4 composite material, can endow the above-mentioned Ni / Fe3O4 composite material or the Ni / Fe3O4 composite material prepared by the above-mentioned method for preparing the Ni / Fe3O4 composite material with the same advantages.

[0144] One embodiment of the present application provides the use of the above Ni / Fe3O4 composite material or the Ni / Fe3O4 composite material prepared by the above preparation method of the Ni / Fe3O4 composite material in the preparation of an electrode. Another embodiment of the present application provides an electrode, comprising a substrate and a catalyst disposed on the surface of the substrate, and the catalyst comprises the above Ni / Fe3O4 composite material or the Ni / Fe3O4 composite material prepared by the above preparation method of the Ni / Fe3O4 composite material.

[0145] One embodiment of the present application provides an electrode, comprising a substrate and a catalyst disposed on the surface of the substrate, and the catalyst comprises the above catalytic material.

[0146] The electrode provided by the present application is used for electrolyzing water to produce hydrogen in an alkaline electrolytic cell, which can reduce the activation energy of the electrolytic water reaction, thereby effectively improving the hydrogen production efficiency and reducing the energy consumption at the same time.

[0147] One embodiment of the present application provides a method for preparing an electrode, comprising the following steps:

[0148] The above Ni / Fe3O4 composite material or the Ni / Fe3O4 composite material prepared by the above preparation method of the Ni / Fe3O4 composite material is disposed on the surface of the substrate to prepare an electrode.

[0149] In some examples, in the method for preparing an electrode, the substrate is an electrode mesh; further, the electrode mesh includes at least one of a nickel wire mesh, nickel foam, a stainless steel mesh, a nickel plate, a stainless steel plate, etc.

[0150] In some examples, in the method for preparing an electrode, the method of disposing the Ni / Fe3O4 composite material on the surface of the substrate includes spraying. Optionally, the spraying is plasma spraying.

[0151] Basic principle of plasma spraying: Using a plasma arc as a heat source, the powdered spraying material is heated to a molten or semi-molten state, and then it is sprayed onto the surface of the pretreated substrate through a high-speed gas flow to form a coating with specific properties. The plasma arc is a high-temperature and high-energy arc generated by gas ionization, which can provide enough heat to quickly melt the spraying material.

[0152] Further, the power of the plasma spraying is 40 kW to 60 kW, the spraying distance is 120 mm to 150 mm, and the powder feeding speed is 100 g / min to 130 g / min.

[0153] It can be understood that the power of plasma spraying includes but is not limited to 40kW, 45kW, 50kW, 55kW, 60kW; the spraying distance includes but is not limited to 120mm, 125mm, 130mm, 135mm, 140mm, 145mm, 150mm; the powder feeding speed includes but is not limited to 100g / min, 105g / min, 110g / min, 115g / min, 120g / min, 125g / min, 130g / min.

[0154] An embodiment of the present application provides an electrolysis device, including the electrode prepared by the above electrode or the preparation method of the above electrode.

[0155] An embodiment of the present application provides an alkaline electrolytic cell, including an electrolytic cell body, a first electrode, a second electrode and an electrolyte. The electrolyte is arranged in the electrolytic cell body, the first electrode and the second electrode are arranged in the electrolyte, and at least one of the first electrode and the second electrode is the above electrode or the electrode prepared by the preparation method of the above electrode.

[0156] The alkaline electrolytic cell provided by the present application is used for electrolyzing water to produce hydrogen, which can reduce the activation energy of the electrolytic water reaction, thereby effectively improving the hydrogen production efficiency and reducing the energy consumption at the same time.

[0157] It can be understood that one of the first electrode and the second electrode is the cathode and the other is the anode. It can also be understood that the alkaline electrolytic cell provided by the present application may further include conventional components in the art, including but not limited to diaphragms, current collectors, etc.; further, the present application does not limit the types and other parameters of components such as the electrolytic cell body, electrolyte, diaphragm, current collector, etc.

[0158] An embodiment of the present application provides a method for electrolyzing water to produce hydrogen, including the following steps:

[0159] Using the above electrolysis device or the above alkaline electrolytic cell to conduct electrolysis to produce hydrogen by passing an electric current.

[0160] Using the above electrolysis device or the above alkaline electrolytic cell to conduct electrolysis to produce hydrogen, the overpotential of the water electrolysis reaction is relatively low, the hydrogen production efficiency is relatively high, and the energy consumption is relatively low.

[0161] In some examples, an electrochemical workstation is used to pass an electric current.

[0162] It can be understood that the method for electrolyzing water to produce hydrogen provided by the present application can reduce the overpotential of the water electrolysis reaction without additionally increasing the operating temperature of the alkaline electrolytic cell, that is, the method for electrolyzing water to produce hydrogen provided by the present application has a relatively low overpotential at the conventional operating temperature (85°C - 90°C) of the electrolytic cell, or can operate at a lower temperature to achieve the same performance, thereby reducing the energy consumption and reducing the corrosion of the electrolytic cell materials.

[0163] In some of these examples, in the method for producing hydrogen by electrolyzing water, the operating temperature of the alkaline electrolyzer is 85°C to 90°C.

[0164] In some of these examples, in the method for producing hydrogen by electrolyzing water, during the process of producing hydrogen by electrolyzing water, it further includes the step of applying a magnetic field to the alkaline electrolyzer. Optionally, the magnetic field is an alternating magnetic field.

[0165] In some of these examples, in the method for producing hydrogen by electrolyzing water, the intensity of the magnetic field is 0 mT to 50 mT.

[0166] It can be understood that the intensity of the magnetic field includes but is not limited to 0 mT, 2 mT, 5 mT, 8 mT, 10 mT, 12 mT, 15 mT, 18 mT, 20 mT, 22 mT, 25 mT, 28 mT, 30 mT, 32 mT, 35 mT, 38 mT, 40 mT, 42 mT, 45 mT, 48 mT, 50 mT. It can also be understood that when the magnetic field intensity is 0, it means no magnetic field is applied; further, compared with not applying a magnetic field, the hydrogen production efficiency is higher and the energy consumption is less during the process of producing hydrogen by electrolyzing water. It can also be understood that there is no sequence for the action of applying a magnetic field, as long as it is ensured that there is a magnetic field during the process of producing hydrogen by electrolyzing water. For example, the magnetic field can be applied before or after power-on, or simultaneously. Optionally, the intensity of the magnetic field is 10 mT to 50 mT. Further, the intensity of the magnetic field is 12 mT to 38 mT.

[0167] The following further describes the present application in detail in conjunction with specific embodiments, but the embodiments of the present application are not limited thereto.

[0168] Example 1

[0169] (1) Preparation of magnetite powder: Add ferrous sulfate and ferric chloride precursors to deionized water, stir evenly to form a mixed solution; transfer the mixed solution to a flask, heat it to 60°C, add sodium hydroxide solution (1 mol / L), stir and react until the mixed solution turns black, then stop stirring. The mass ratios of ferrous sulfate, ferric chloride, sodium hydroxide solution and deionized water are 3.5:6.5:10:100 respectively. After aging for 40 min, transfer the aged solution to a hydrothermal reaction kettle and react at 160°C for 4 h. After the reaction, wash, filter and dry the solution to obtain Fe3O4 nanoparticles, that is, magnetite powder;

[0170] (2)Preparation of Ni / Fe₃O₄ powder: The Fe₃O₄ powder prepared in step (1) was dispersed in an ethylene glycol aqueous solution. After adding a nickel chloride precursor and stirring to form a homogeneous solution, ammonia water (20 wt%) was added. The solution was transferred to a hydrothermal reaction kettle and reacted at 90 °C for 3 h. The mass ratio of the Fe₃O₄ powder to the nickel precursor, ammonia water, and ethylene glycol aqueous solution (25 wt%) was 1:2.6:5:100. After the reaction, it was washed and dried to obtain Ni / Fe₃O₄ powder (primary particles with a particle size of about 80 nm), and the mass ratio of Fe₃O₄ to Ni was 1:1; among them, the transmission electron microscope image of the Ni / Fe₃O₄ primary particles is as shown in Figure 1 shown, and the mapping of the Ni / Fe₃O₄ primary particles is as shown in Figure 2 shown. It can be seen from Figures 1 - 2 that the Ni / Fe₃O₄ primary particles are core-shell structures, and nickel is coated on the surface of Fe₃O₄.

[0171] (3)Preparation of Ni / Fe₃O₄ composite material: After taking the Ni / Fe₃O₄ powder prepared in step (2) and dispersing it in water, a binder polyvinyl alcohol solution and an antifoaming agent n-butanol were added and placed in a ball mill for ball milling to obtain a homogeneous slurry. Among them, the mass ratio of the Ni / Fe₃O₄ powder, water, polyvinyl alcohol solution (10 wt.%), and n-butanol was 1:1.5:0.04:0.005. The slurry was fed into an atomizer to be atomized into droplets, and the droplets were dried into spherical particles at high temperature (i.e., spray drying). The obtained spherical powder was vacuum sintered at 700 °C for 5 hours and sieved to obtain a Ni / Fe₃O₄ composite material with a particle size of 30 μm - 50 μm (the Ni / Fe₃O₄ composite material is secondary particles with a particle size of 30 μm - 50 μm); among them, the scanning electron microscope image of the Ni / Fe₃O₄ secondary particles is as shown in Figure 3 shown;

[0172] (4)Preparation of Ni / Fe₃O₄ electrode: The Ni / Fe₃O₄ composite material prepared in step (3) was sent into a plasma flame stream, and the molten droplets were sprayed on a nickel wire mesh. The plasma spraying power was set at 45 kW, the spraying distance was 130 mm, and the feeding speed was 120 g / min to obtain a Ni / Fe₃O₄ electrode.

[0173] Example 2

[0174] It is basically the same as Example 1, except that in the Ni / Fe₃O₄ powder prepared in step (2), the mass ratio of Fe₃O₄ to Ni is 1:2, specifically as follows:

[0175] (1)Preparation of Fe₃O₄ powder: Add ferrous sulfate and ferric chloride precursors to deionized water, stir evenly to form a mixed solution; transfer the mixed solution to a flask, heat it to 60 °C, add sodium hydroxide solution (1 mol / L), stir and react until the mixed solution turns black, then stop stirring. The mass ratios of ferrous sulfate, ferric chloride, sodium hydroxide solution and deionized water are 3.5:6.5:10:100 respectively. After aging for 40 min, transfer the aged solution to a hydrothermal reactor, react at 160 °C for 4 h. After the reaction, wash, filter and dry the solution to obtain Fe₃O₄ nanoparticles, that is, Fe₃O₄ powder;

[0176] (2)Preparation of Ni / Fe₃O₄ powder: Disperse the Fe₃O₄ powder prepared in step (1) into an ethylene glycol aqueous solution, add nickel chloride precursor, stir to form a homogeneous solution, then add ammonia water (20 wt%), transfer the solution to a hydrothermal reactor, and react at 90 °C for 3 h. The mass ratios of Fe₃O₄ powder to nickel precursor, ammonia water and ethylene glycol aqueous solution (25 wt%) are 1:5.3:5:100. After the reaction, wash and dry to obtain Ni / Fe₃O₄ powder (primary particles, particle size about 80 nm), and the mass ratio of Fe₃O₄ to Ni is about 1:2;

[0177] (3)Preparation of Ni / Fe₃O₄ composite: Take the Ni / Fe₃O₄ powder prepared in step (2), disperse it in water, add binder polyvinyl alcohol solution and defoamer n-butanol, and place it in a ball mill to obtain a uniform slurry. Among them, the mass ratios of Ni / Fe₃O₄ powder, water, polyvinyl alcohol solution (10 wt.%), and n-butanol are 1:1.5:0.04:0.005. Transport the slurry to an atomizer to atomize it into droplets, and the droplets are dried into spherical particles at high temperature. Sinter the obtained spherical powder in vacuum at 700 °C for 5 h, and obtain Ni / Fe₃O₄ composite (secondary particles) with a particle size of 30 μm - 50 μm by sieving;

[0178] (4)Preparation of Ni / Fe₃O₄ electrode: Feed the Ni / Fe₃O₄ composite prepared in step (3) into a plasma flame, and spray the molten droplets on a nickel wire mesh. Set the plasma spraying power to 45 kW, the spraying distance to 130 mm, and the powder feeding speed to 120 g / min to obtain the Ni / Fe₃O₄ electrode.

[0179] Example 3

[0180] It is basically the same as Example 1, the difference is that in the Ni / Fe₃O₄ powder prepared in step (2), the mass ratio of Fe₃O₄ to Ni is 1:0.3, specifically as follows:

[0181] (1)Preparation of Fe₃O₄ powder: Add ferrous sulfate and ferric chloride precursors to deionized water, stir evenly to form a mixed solution; transfer the mixed solution to a flask, heat it to 60 °C, add sodium hydroxide solution (1 mol / L), stir and react until the mixed solution turns black, then stop stirring. The mass ratios of ferrous sulfate, ferric chloride, sodium hydroxide solution and deionized water are 3.5:6.5:10:100 respectively. After aging for 40 min, transfer the aged solution to a hydrothermal reactor and react at 160 °C for 4 h. After the reaction, wash, filter and dry the solution to obtain Fe₃O₄ nanoparticles, that is, Fe₃O₄ powder;

[0182] (2)Preparation of Ni / Fe₃O₄ powder: Disperse the Fe₃O₄ powder prepared in step (1) into an ethylene glycol aqueous solution, add nickel chloride precursor, stir to form a homogeneous solution, then add ammonia water (20 wt%), transfer the solution to a hydrothermal reactor and react at 90 °C for 3 h. The mass ratios of Fe₃O₄ powder, nickel precursor, ammonia water and ethylene glycol aqueous solution (25 wt%) are 1:0.8:5:100. After the reaction, wash and dry to obtain Ni / Fe₃O₄ powder (primary particles, particle size about 80 nm), and the mass ratio of Fe₃O₄ to Ni is about 1:0.3;

[0183] (3)Preparation of Ni / Fe₃O₄ composite: Take the Ni / Fe₃O₄ powder prepared in step (2), disperse it in water, add binder polyvinyl alcohol solution and defoamer n-butanol, and place it in a ball mill to obtain a uniform slurry. Among them, the mass ratios of Ni / Fe₃O₄ powder, water, polyvinyl alcohol solution (10 wt.%), and n-butanol are 1:1.5:0.04:0.005. Transfer the slurry to an atomizer to atomize it into droplets, and the droplets are dried into spherical particles at high temperature. Sinter the obtained spherical powder in vacuum at 700 °C for 5 h, and obtain Ni / Fe₃O₄ composite (secondary particles) with a particle size of 30 μm - 50 μm by sieving;

[0184] (4)Preparation of Ni / Fe₃O₄ electrode: Send the Ni / Fe₃O₄ composite prepared in step (3) into a plasma flame, and spray the molten droplets on a nickel wire mesh. The plasma spraying power is set at 45 kW, the spraying distance is 130 mm, and the feeding speed is 120 g / min to obtain a Ni / Fe₃O₄ electrode.

[0185] Example 4

[0186] It is basically the same as Example 1, the difference is that in step (3), Ni / Fe₃O₄ composite (secondary particles) with a particle size of 60 μm - 80 μm is obtained by sieving, specifically as follows:

[0187] (1) Preparation of ferroferric oxide powder: Add ferrous sulfate and ferric chloride precursors to deionized water and stir to form a mixed solution; transfer the mixed solution to a flask and heat to 60°C, add sodium hydroxide solution (1 mol / L), stir and react until the mixed solution turns black and then stop stirring, wherein the mass ratio of ferrous sulfate, ferric chloride, sodium hydroxide solution and deionized water is 3.5:6.5:10:100 respectively. After aging for 40 minutes, transfer the aged solution to a hydrothermal reactor and react at 160°C for 4 hours. After the reaction is completed, wash, filter and dry the solution to obtain Fe3O4 nanoparticles, i.e., ferroferric oxide powder;

[0188] (2) Preparation of Ni / Fe3O4 powder: The ferroferric oxide powder prepared in step (1) was dispersed in an ethylene glycol aqueous solution, and a nickel chloride precursor was added. After stirring to form a uniform solution, an ammonia solution (20 wt%) was added. The solution was transferred to a hydrothermal reactor and reacted at 90°C for 3 h. The mass ratio of the ferroferric oxide powder to the nickel precursor, the ammonia solution and the ethylene glycol aqueous solution (25 wt%) was 1:2.6:5:100. After the reaction, the powder was washed and dried to obtain Ni / Fe3O4 powder (primary particles with a particle size of about 80 nm). The mass ratio of Fe3O4 to Ni was about 1:1.

[0189] (3) Preparation of Ni / Fe3O4 composite material: Disperse the Ni / Fe3O4 powder prepared in step (2) into water, add a binder polyvinyl alcohol solution and a defoaming agent n-butanol, and mill in a ball mill to obtain a uniform slurry, wherein the mass ratio of Ni / Fe3O4 powder, water, polyvinyl alcohol solution (10 wt.%), and n-butanol is 1:1.5:0.04:0.005. The slurry is transported to an atomizer and atomized into droplets. The droplets are dried at high temperature to form spherical particles. The obtained spherical powder is vacuum sintered at 700°C for 5 hours, and a Ni / Fe3O4 composite material (secondary particles) with a particle size of 60 μm to 80 μm is obtained by sieving.

[0190] (4) Preparation of Ni / Fe3O4 electrode: The Ni / Fe3O4 composite material prepared in step (3) was fed into the plasma flame flow, and the molten droplets were sprayed onto the nickel wire mesh. The plasma spraying power was set to 45 kW, the spraying distance was 130 mm, and the feeding speed was 120 g / min to obtain a Ni / Fe3O4 electrode.

[0191] Example 5

[0192] The method is basically the same as Example 1, except that in step (3), the Ni / Fe3O4 composite material (secondary particles) with a particle size of 10 μm to 25 μm is obtained by sieving, as follows:

[0193] (1) Preparation of Fe₃O₄ powder: Ferrous sulfate and ferric chloride precursors were added to deionized water and stirred evenly to form a mixed solution. The mixed solution was transferred to a flask and heated to 60 °C, and then sodium hydroxide solution (1 mol / L) was added. Stirring was stopped after the mixed solution turned black. The mass ratios of ferrous sulfate, ferric chloride, sodium hydroxide solution and deionized water were 3.5:6.5:10:100 respectively. After aging for 40 min, the aged solution was transferred to a hydrothermal reactor and reacted at 160 °C for 4 h. After the reaction, the solution was washed, filtered and dried to obtain Fe₃O₄ nanoparticles, namely Fe₃O₄ powder;

[0194] (2) Preparation of Ni / Fe₃O₄ powder: The Fe₃O₄ powder prepared in step (1) was dispersed in an ethylene glycol aqueous solution, and nickel chloride precursor was added. After stirring to form a homogeneous solution, ammonia water (20 wt%) was added. The solution was transferred to a hydrothermal reactor and reacted at 90 °C for 3 h. The mass ratios of Fe₃O₄ powder, nickel precursor, ammonia water and ethylene glycol aqueous solution (25 wt%) were 1:2.6:5:100. After the reaction, it was washed and dried to obtain Ni / Fe₃O₄ powder (primary particles, particle size about 80 nm), and the mass ratio of Fe₃O₄ to Ni was 1:1;

[0195] (3) Preparation of Ni / Fe₃O₄ composite: The Ni / Fe₃O₄ powder prepared in step (2) was dispersed in water, and then a binder polyvinyl alcohol solution and an antifoaming agent n-butanol were added and ball milled in a ball mill to obtain a homogeneous slurry. Among them, the mass ratios of Ni / Fe₃O₄ powder, water, polyvinyl alcohol solution (10 wt.%), and n-butanol were 1:1.5:0.04:0.005. The slurry was fed into an atomizer to be atomized into droplets, and the droplets were dried into spherical particles at high temperature. The obtained spherical powder was vacuum sintered at 700 °C for 5 h and sieved to obtain Ni / Fe₃O₄ composite (secondary particles) with a particle size of 10 μm - 25 μm;

[0196] (4) Preparation of Ni / Fe₃O₄ electrode: The Ni / Fe₃O₄ composite prepared in step (3) was fed into a plasma flame, and the molten droplets were sprayed on a nickel wire mesh. The plasma spraying power was set at 45 kW, the spraying distance was 130 mm, and the feeding speed was 120 g / min to obtain a Ni / Fe₃O₄ electrode.

[0197] Comparative Example 1

[0198] (1)Preparation of Ni nano-powder: Nickel chloride precursor was added to polyethylene glycol solution. After stirring to form a homogeneous solution, ammonia water (20 wt%) was added. The solution was transferred to a hydrothermal reactor and reacted at 90 °C for 3 h. The mass ratio of nickel precursor, ammonia water and ethylene glycol aqueous solution (25 wt%) was 1:5:100. After the reaction, it was washed and dried to obtain Ni nano-powder (primary particles, with a particle size of about 60 nm).

[0199] (2)Preparation of Ni agglomerated powder: The Ni nano-powder prepared in step (1) was dispersed in water, and then a binder polyvinyl alcohol solution and an antifoaming agent n-butanol were added, and the mixture was ball-milled in a ball mill to obtain a uniform slurry. Among them, the mass ratio of Ni nano-powder, water, polyvinyl alcohol solution (10 wt.%), and n-butanol was 1:1.5:0.04:0.005. The slurry was fed into an atomizer to be atomized into droplets, and the droplets were dried into spherical particles at high temperature. The obtained spherical powder was vacuum sintered at 700 °C for 5 h, and Ni agglomerated powder (secondary particles) with a particle size of 30 μm - 50 μm was obtained by sieving;

[0200] (3)Preparation of Ni electrode: The Ni agglomerated powder prepared in step (2) was fed into a plasma flame, and the molten droplets were sprayed on a nickel wire mesh. The plasma spraying power was set at 45 kW, the spraying distance was 130 mm, and the feeding speed was 120 g / min to obtain a Ni electrode.

[0201] Comparative Example 2

[0202] It was basically the same as Example 1, except that in the step of preparing the Ni / Fe3O4 electrode, step (3) was omitted, and the Ni / Fe3O4 powder (primary particles) prepared in step (2) was fed into a plasma flame, and the molten droplets were sprayed on the electrode mesh to obtain a Ni / Fe3O4 electrode, specifically as follows:

[0203] (1)Preparation of iron oxide powder: Ferrous sulfate and ferric chloride precursors were added to deionized water in proportion and stirred evenly to form a mixed solution; the mixed solution was transferred to a flask and heated to 60 °C, and sodium hydroxide solution (1 mol / L) was added. Stirring was stopped after the reaction until the mixed solution turned black. The mass ratio of ferrous sulfate, ferric chloride, sodium hydroxide solution and deionized water was 3.5:6.5:10:100 respectively. After aging for 40 min, the aged solution was transferred to a hydrothermal reactor and reacted at 160 °C for 4 h. After the reaction, the solution was washed, filtered and dried to obtain Fe3O4 nanoparticles, that is, iron oxide powder;

[0204] (2)Preparation of Ni / Fe3O4 powder: The Fe3O4 powder prepared in step (1) was dispersed in an ethylene glycol aqueous solution. After adding a nickel chloride precursor and stirring to form a homogeneous solution, ammonia water (20 wt%) was added. The solution was transferred to a hydrothermal reaction kettle and reacted at 90 °C for 3 h. The mass ratio of the Fe3O4 powder to the nickel precursor, ammonia water, and ethylene glycol aqueous solution (25 wt%) was 1:2.6:5:100. After the reaction, it was washed and dried to obtain Ni / Fe3O4 powder (primary particles, with a particle size of about 80 nm), and the mass ratio of Fe3O4 to Ni was 1:1;

[0205] (3)Preparation of Ni / Fe3O4 electrode: The Ni / Fe3O4 powder prepared in step (2) was fed into a plasma flame, and the molten droplets were sprayed onto a nickel wire mesh. The plasma spraying power was set at 45 kW, the spraying distance was 130 mm, and the feeding speed was 120 g / min to obtain a Ni / Fe3O4 electrode.

[0206] Comparative Example 3

[0207] Deposit Fe3O4 on the upper surface of the electrode mesh and then deposit nickel to prepare the electrode, specifically as follows:

[0208] (1)The nickel wire mesh was immersed in acetone and ultrasonically cleaned for 15 minutes (to remove surface oil), rinsed 3 times with deionized water, and dried with nitrogen; Concentrated HNO3 (65%) was prepared and the nickel wire mesh was soaked at room temperature for 10 minutes to remove the oxide layer; After rinsing, it was placed in a drying oven and baked at 120 °C for 30 minutes for standby;

[0209] (2)Ferrous sulfate and ferric chloride precursors were added to deionized water in proportion and stirred evenly to form a mixed solution; The mixed solution was transferred to a flask and heated to 60 °C, and a nickel wire mesh was placed in it. Sodium hydroxide solution (1 mol / L) was added. The mass ratios of ferrous sulfate, ferric chloride, sodium hydroxide solution, and deionized water were 3.5:6.5:10:100 respectively. After aging for 40 min, the aged solution was transferred to a hydrothermal reaction kettle and reacted at 160 °C for 4 h. After the reaction, the solution was washed, filtered, and dried to obtain a nickel electrode loaded with Fe3O4;

[0210] (3)Preparation of Ni / Fe3O4-loaded nickel electrode: The nickel chloride precursor was dispersed in an ethylene glycol solution and stirred to form a homogeneous solution. Then, the Ni / Fe3O4-loaded nickel electrode was immersed in the solution, and ammonia water (20 wt%) was added. The solution was transferred to a hydrothermal reaction kettle and reacted at 90 °C for 3 h. The mass ratio of the nickel precursor, ammonia water, and ethylene glycol aqueous solution (25 wt%) was 2.6:5:100. After the reaction, it was washed and dried to obtain a Ni / Fe3O4-loaded nickel electrode, and the mass ratio of Fe3O4 to Ni was 1:1.

[0211] The electrodes prepared in each example and comparative example were used as working electrodes, Hg / HgO was used as the reference electrode, and a nickel wire was used as the counter electrode to assemble a three-electrode electrolytic cell. An electrochemical workstation was used to measure the hydrogen evolution overpotential and oxygen evolution overpotential of the electrodes at a current density of 500 mA / cm 2 . The tests of Examples 1-1 to 1-5 refer to the tests of the electrodes prepared in Example 1 under different magnetic field intensities. Comparative Examples 1-1 and 1-2 refer to the tests of the electrodes prepared in Comparative Example 1 under different magnetic field intensities. An alternating magnetic field was applied to the system during the test process, as shown in Table 1 specifically.

[0212] Table 1

[0213]

[0214] As can be seen from Table 1, compared with Comparative Example 1 where Ni agglomerated powder was sprayed onto the electrode mesh as the electrode, in the examples of the present application, primary particles with a core-shell structure (the core is Fe3O4 and the shell is Ni) were made into secondary particles and then sprayed onto the electrode mesh as the electrode, which can effectively reduce the overpotential of the water electrolysis reaction, thereby improving the hydrogen production efficiency, without the need to increase the operating temperature of the electrolytic cell, reducing energy consumption, and not damaging the diaphragm and not corroding the cell body.

[0215] Compared with Example 1, in Comparative Example 2, secondary particles were not made, and primary particles with a core-shell structure (the core is Fe3O4 and the shell is Ni) were directly sprayed onto the electrode mesh. The particle size was smaller and the powder spraying rate was lower, seriously reducing the electrode performance; in Comparative Example 3, a Ni / Fe3O4 catalytic layer was directly deposited on the nickel wire mesh by a hydrothermal method, and no core-shell structure was formed, and no conductive network could be formed, resulting in lower performance.

[0216] As can be seen from Examples 1-1 to 1-5, using the Ni / Fe3O4 composite material prepared in Example 1 as the catalytic material to prepare the electrode, by applying an alternating magnetic field, the overpotential of the water electrolysis reaction can be effectively reduced; and within a suitable magnetic field intensity range, as the magnetic field intensity increases, the overpotential of the water electrolysis reaction decreases more significantly.

[0217] As can be seen from Examples 1 to 3, controlling the mass ratio of Fe3O4 to Ni within a suitable range enables the electrode to balance conductivity and magnetothermal performance, thereby effectively reducing the overpotential of the water electrolysis reaction; as can be seen from Examples 1, 4, and 5, controlling the particle size of the Ni / Fe3O4 composite material (secondary particles) sprayed on the nickel wire mesh within a suitable range ensures the active area of the electrode and effectively reduces the overpotential of the water electrolysis reaction.

[0218] The technical features of the above-described embodiments can be combined arbitrarily. For the sake of brevity of description, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, it should be considered as falling within the scope described in this specification.

[0219] The above-described embodiments merely represent several implementation manners of the present application, which are convenient for understanding the technical solutions of the present application specifically and in detail, but should not be construed as a limitation on the protection scope of the invention patent. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present application, several modifications and improvements can still be made, and these all belong to the protection scope of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the protection scope of the appended claims of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the content of the appended claims, and the description can be used to interpret the content of the claims.

Claims

1. A Ni / Fe3O4 composite material, characterized in that: The invention comprises secondary particles, wherein the secondary particles comprise stacked primary particles, the primary particles comprise an inner core and an outer shell arranged on the surface of the inner core, the inner core comprises ferrosoferric oxide, and the outer shell comprises nickel.

2. The Ni / Fe3O4 composite material according to claim 1, characterized in that The particle size of the secondary particles is 10 μm to 100 μm.

3. The Ni / Fe3O4 composite material according to claim 1, characterized in that The particle size of the primary particles is 45 nm to 125 nm.

4. The Ni / Fe3O4 composite material according to claim 1, characterized in that In the primary particles, the mass ratio of the ferroferric oxide to the nickel element is 1:0.2-3; And / or, the particle size of the ferrosoferric oxide is 30 nm to 80 nm.

5. The Ni / Fe3O4 composite material according to any one of claims 1 to 4, characterized in that: The Ni / Fe3O4 composite material has a current density of 500 mA / cm 2 The overpotential for hydrogen evolution is ≤335 mV, and the overpotential for oxygen evolution is ≤433 mV.

6. A method for preparing a Ni / Fe3O4 composite material, characterized in that: The following steps are involved: Mixing Ni / Fe3O4 powder, a binder and a solvent to prepare a slurry; the Ni / Fe3O4 powder comprises a core and a shell disposed on the surface of the core, the core comprises ferrosoferric oxide, and the shell comprises nickel; The slurry is spray-dried and sintered in sequence to obtain a Ni / Fe3O4 composite material.

7. The method for preparing the Ni / Fe3O4 composite material according to claim 6, characterized in that: The sintering temperature is 500°C to 900°C; and / or, performing the sintering process under vacuum conditions; and / or, the air inlet temperature of the spray drying is 250° C. to 350° C., the air outlet temperature of the spray drying is 150° C. to 200° C., and the air flow pressure of the spray drying is 30 kPa to 100 kPa; and / or, the Ni / Fe3O4 powder is a primary particle; And / or, the particle size of the Ni / Fe3O4 powder is 45 nm to 120 nm; and / or, the binder comprises polyvinyl alcohol; And / or, the mass ratio of the binder to the Ni / Fe3O4 powder is 0.002-0.006:1; And / or, the solvent comprises water.

8. The method for preparing the Ni / Fe3O4 composite material according to claim 6, characterized in that: The preparation of the Ni / Fe3O4 powder comprises the following steps: The ferroferric oxide powder, a nickel precursor, a reducing agent and a pH regulator are mixed to undergo a hydrothermal reaction, and the nickel precursor is reduced on the surface of the ferroferric oxide powder to generate a nickel element, thereby preparing a Ni / Fe3O4 powder.

9. The method for preparing the Ni / Fe3O4 composite material according to claim 8, characterized in that: The temperature of the hydrothermal reaction is 80°C to 120°C; and / or, the nickel precursor comprises at least one of nickel chloride, nickel sulfate and nickel nitrate; And / or, the mass ratio of the nickel precursor to the ferroferric oxide powder is 0.6-8:1; and / or, the reducing agent comprises at least one of ethylene glycol, sodium borohydride and sodium citrate; And / or, the mass ratio of the reducing agent to the ferroferric oxide powder is 20-30:1; And / or, the pH adjuster includes aqueous ammonia; And / or, the mass ratio of the pH regulator to the nickel precursor is 2-8:

1.

10. A catalytic material, characterized in that: It comprises the Ni / Fe3O4 composite material as described in any one of claims 1 to 5 or the Ni / Fe3O4 composite material prepared by the preparation method as described in any one of claims 6 to 9.

11. An electrode, characterized in that: It comprises a substrate and a catalyst arranged on the surface of the substrate, wherein the catalyst comprises the catalytic material as claimed in claim 10.

12. A method for preparing an electrode, characterized in that: The following steps are involved: The Ni / Fe3O4 composite material as claimed in any one of claims 1 to 5 or the Ni / Fe3O4 composite material prepared by the preparation method as claimed in any one of claims 6 to 9 is arranged on the surface of a substrate to prepare an electrode.

13. An alkaline electrolytic cell, characterized in that: It includes an electrolytic cell body, a first electrode, a second electrode and an electrolyte, wherein the electrolyte is arranged in the electrolytic cell body, the first electrode and the second electrode are arranged in the electrolyte, and at least one of the first electrode and the second electrode is the electrode as claimed in claim 11 or the electrode prepared by the preparation method as claimed in claim 12.

14. A method for producing hydrogen by electrolysis of water, characterized in that: The following steps are involved: The alkaline electrolytic cell according to claim 13 is energized to electrolyze water to produce hydrogen.

15. The method for producing hydrogen by electrolysis of water according to claim 14, characterized in that: The process of producing hydrogen by electrolyzing water also includes a step of applying a magnetic field to the alkaline electrolytic cell.

Citation Information

Patent Citations

  • Double-metal composite material as well as preparing method and application thereof

    CN107012473A

  • Vermicular Ni / Ni<x>Fe<1-x>O<y> hydrogen evolution catalyst and preparation method thereof

    CN109985629A

  • Core-shell structured nanoparticle having hard-soft magnetic heterostructure, magnet prepared with said nanoparticle, and preparing method thereof

    WO2013115495A1